The Role of Human Rights Watch in Reducing Child Labor in Indonesia's Tobacco Fields (2014-2017) - Tika Sabrina (Global Local Interactions: Journal of International Relations, 2022)
This research discusses about one of the roles of NGOs (Non-Governmental Organizations) in overcoming the issue of child labor in tobacco fields in Indonesia. This type of research is descriptive with a research question, namely "How did the Human Rights Watch Contribute to Minimize Child Labor in Indonesia's Tobacco Fields (2014-2017)?". This research uses the theory of The Role of NGOs which is the main framework of this research and the supporting theory uses namely The Concept of Human Security which explains that the issue of child labor in tobacco fields in Indonesia is included in humanitarian issues that are closely related to human rights. The results of the research shows that HRW (Human Rights Watch) as an international non-governmental organization, which is engaged in human rights issues, has 2 roles in dealing with child labor in tobacco fields in Indonesia, namely Partnership and Catalysts. This research takes a timeline starting from 2014 where HRW began conducting research on child labor cases, until 2017 along with the ratification of the Roadmap Towards Indonesia Free Child Labor 2022, HRW submitted and published the results of their research